2009
DOI: 10.1063/1.3079503
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of an atmospheric pressure plasma plume

Abstract: The “plasma bullet” behavior of atmospheric pressure plasma plumes has recently attracted significant interest. In this paper, a specially designed plasma jet device is used to study this phenomenon. It is found that a helium primary plasma can propagate through the wall of a dielectric tube and keep propagating inside the dielectric tube (secondary plasma). High-speed photographs show that the primary plasma disappears before the secondary plasma starts to propagate. Both plumes propagate at a hypersonic spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
1
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(52 citation statements)
references
References 36 publications
4
40
1
7
Order By: Relevance
“…Typical oxidation techniques are plasma exposure [1][2][3] and ultraviolet (UV) light irradiation. [4][5][6][7] In the present paper, modification of polyester, PET and PEN, surfaces was performed using an atmospheric-pressure plasma (APP) jet, [8][9][10][11] which can perform the treatment in a very short time and in an open space without any limitations on the sample size. Nitrogen gas was used as the reactive gas species because we found it effective for hydrophilization of the polymer surface.…”
Section: Introductionmentioning
confidence: 99%
“…Typical oxidation techniques are plasma exposure [1][2][3] and ultraviolet (UV) light irradiation. [4][5][6][7] In the present paper, modification of polyester, PET and PEN, surfaces was performed using an atmospheric-pressure plasma (APP) jet, [8][9][10][11] which can perform the treatment in a very short time and in an open space without any limitations on the sample size. Nitrogen gas was used as the reactive gas species because we found it effective for hydrophilization of the polymer surface.…”
Section: Introductionmentioning
confidence: 99%
“…Bárdos and Baránková [14] have described the difference between low-pressure and atmospheric pressure plasmas and reviewed limitation and new abilities of atmospheric pressure plasma. Atmospheric pressure plasma (APP) jet devices have attracted significant attention [17][18][19][20][21] because they generate plasma plumes in open space, have no limitations on the sizes of the objects to be treated, and can achieve continuous in-line material processing at high speed. Schütze et al [17] have reported that the APP jet exhibits the great similarity to a low-pressure glow discharge compared with other plasmas and can be used in a number of materials applications that are now limited to vacuum.…”
Section: Introductionmentioning
confidence: 99%
“…There are three mechanisms to contribute to the ionization front velocity: electron diffusion, ponderomotive force, and breakdown wave. 39,40 The ionization wave front velocity due to electron diffusion can be expressed as υ = 2(v i D a ) 1/2 , where v i is the ionization frequency and D a is the ambipolar diffusion coefficient. For a nonequilibrium plasma, D a is expressed as D a = μ + kBT e /e, where μ + is the ion mobility and T e is the electron temperature.…”
Section: Plume Generationmentioning
confidence: 99%